``THE EVALUATION PROCESS AND ITS INFLUENCE ON THE LEARNING OF THE ENGLISH LANGUAGE WITH THE STUDENTS OF 8TH ,9TH , AND 10TH YEARS OF BASIC EDUCATION AT ´´ BERNARDO VALDIVIESO HIGH SCHOOL NIGHT SECTION, ACADEMIC PERIOD 2009-2010´´ - ROSALES ALVAREZ, TYRONE FERNANDO (2011)
This research work entitled: THE EVALUATION PROCESS AND ITS INFLUENCE ON THE LEARNING OF THE ENGLISH LANGUAGE WITH STUDENTS OF 8th , 9th AND 10th YEARS OF BASIC EDUCATION AT BERNARDO VALDIVIESO HIGH SCHOOL NIGTH SECTION ACADEMIC PERIOD 2009-2010 ,whose general objective was: to determine the influence on the evaluation process to the learning of the English language with the students of 8th ,9th and 10th years of basic education at Bernardo Valdivieso high school night section academic period 2009 – 2010 has been developed with the purpose of discovering if the teachers use correct evaluation techniques, to achieve a good outcomes on the learning of the English language. To reach this, it is used some methods, such as the scientific, descriptive, analytic-synthetic and explicative, the same ones that and they have helped to develop every part of the research process. To collect the information of the researched high school, it is used the technique of the survey. It was applied to 5 teachers and 146 students. Then to represent the obtained data there is a descriptive statistics, which let us present the information on graphs and charts, for an easier understanding. The results of this research work are: the kinds of evaluation and assessment procedures applied by the teachers are not diversified as they should be and the evaluation strategies applied by them are traditional what affects the learning of the English language to the students.